Influence of Capital Structure, Profitability, and Liquidity on the Value of Transportation and Logistics Companies Listed on the IDX 2022-2 - Elsanti Nur Safitri; Sugiyanta; Sri Wahyuni (JOBS (Jurnal Of Business Studies), 2025)
Throughout the period 2022–2024, the average Price to Book Value (PBV) of companies in the transportation and logistics sector experienced a consistent downward trend. This decline was accompanied by a weakening trend in the IDXTRANS stock index, indicating financial dynamics that require further scrutiny, particularly regarding capital structure, profitability, and liquidity. This study aims to examine the effect of capital structure, profitability, and liquidity on the value of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange during the period 2022–2024. Capital structure was measured using the Debt to Equity (DER) ratio, profitability using Return on Assets (ROA), and liquidity using the Current Ratio (CR), as well as firm value, proxied by PBV. The sample was obtained through purposive sampling of 19 companies with a total of 228 quarterly observations. Data analysis was performed using multiple linear regression, t- and F-tests, and the coefficient of determination (R²) calculation. The findings of this study indicate that individually, profitability and capital structure have a significant positive impact on firm value. Conversely, the liquidity variable does not show a significant effect. Simultaneously, all three variables significantly influence firm value. The results of this study provide a strategic foundation for management, investors, and other stakeholders in examining and determining significant financial indicators in the process of assessing a company's market value